Theoretical Framework of a Variational Formulation for Nonlinear Heat Transfer with Phase Changes. (14th February 2013) - Feulvarch, Eric; Roux, Jean-Christophe; Bergheau, Jean-Michel
Abstract : This paper discusses mathematical results for a variational formulation dedicated to heat transfer with phase changes. Practical finite element experiences show that the studied formulation can lead to difficulties for the numerical resolution at each time step. The aim of the paper is to show that such numerical pathologies do not come from the basic variational formulation by showing existence and uniqueness of the solution.